Jews and New Christians in the Making of the Atlantic World in the 16th–17th Centuries - Szlajfer, Henryk, author.
1 online resource (354 pages)
Keywords: Amsterdam Jews appeared up to the mid-17th century as Braudelian “great Jewish merchants.” However, the New Christians, heretic judaizantes in the eyes of the Inquisition, dispersed around the world group sui generis , were equally crucial. Their religious identities were fluid, but at the same time they and the “new Jews” from Amsterdam formed a part of economic modernity epitomized by the rebellious Netherlands and the developing Atlantic economy. At the height of their influence they played a pivotal, albeit controversial, role in the rising slave trade. The disappearance of New Christians in Latin America had to be contextualised with inquisitorial persecutions and growing competition in mind.